Fibromyalgia: a clinical review - Clauw, Daniel J (JAMA : the journal of the American Medical Association, 2014)
Fibromyalgia is present in as much as 2% to 8% of the population, is characterized by widespread pain, and is often accompanied by fatigue, memory problems, and sleep disturbances. To review the epidemiology, pathophysiology, diagnosis, and treatment of fibromyalgia. The medical literature on fibromyalgia was reviewed from 1955 to March 2014 via MEDLINE and the Cochrane Central Registry of Controlled Trials, with an emphasis on meta-analyses and contemporary evidence-based treatment guidelines. Treatment recommendations are based on the most recent evidence-based guidelines from the Canadian Pain Society and graded from 1 to 5 based on the level of available evidence. Numerous treatments are available for managing fibromyalgia that are supported by high-quality evidence. These include nonpharmacological therapies (education, exercise, cognitive behavioral therapy) and pharmacological therapies (tricyclics, serotonin norepinephrine reuptake inhibitors, and gabapentinoids). Fibromyalgia and other "centralized" pain states are much better understood now than ever before. Fibromyalgia may be considered as a discrete diagnosis or as a constellation of symptoms characterized by central nervous system pain amplification with concomitant fatigue, memory problems, and sleep and mood disturbances. Effective treatment for fibromyalgia is now possible.